Interrelationship of hepatitis C virus genotypes with patient characteristics in Bahrain - Abdulla MA (Dove Medical Press, 2017)
Maheeba A Abdulla,1 Eman A Murad,1 Hend A Aljenaidi,1 Duha R Aljowder,1 Omar IK Aljeeran,1 Eman Farid,2 Jehad R Al Qamish3 1Department of Internal Medicine, 2Department of Pathology, Salmaniya Medical Complex, 3Department of Internal Medicine, Ibn Al Nafees Hospital, Manama, Bahrain Aim: Hepatitis C virus (HCV) shows genotype-based variation in prevalence across geographical regions. This study was conducted to understand the clinical interrelationship of HCV genotypes with patient characteristics. Methods: Medical records of 122 patients positive for HCV RNA test collected during 2013 and 2014 were included for analysis. Only adults were included in the study. HCV RNA extraction and genotyping was done as part of the routine diagnostic requirements. The association of continuous and categorical variables with genotypes was analyzed through analysis of variance and chi-square tests, respectively. Results: Of the 122 patients selected, 103 were Bahrainis, 18 non-Bahrainis, and 1 was unregistered. Genotype 1 was the predominant (53%) one, followed by types 3 (23%) and 4 (20%). Classical symptoms, clinical signs, liver function test, and ultrasonographic results were recorded. Cirrhosis and ascites showed significant variation across genotypes. Although alanine transaminase, total bilirubin, and albumin levels were increased, gamma-glutamyltransferase and alkaline phosphatase levels were normal. About 12% of the subjects were alcohol users, 4% were positive for HIV infection and 2.4% were positive for hepatitis B virus infection. The circulating HCV RNA load was at medium-level in the study cohort and showed significant association with the HCV genotypes and subtypes. Patients with genotype 1a had 6 times more load than patients with type 4 (P<0.05). Conclusion: This study reconfirmed the incidence and distribution of different genotypes in Bahrain population, and delineated the relationship of HCV RNA viral load with the severity of liver disease in our cohort. Keywords: hepatitis C virus, hepatitis, Bahrain